2022
DOI: 10.1108/ajeb-01-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

Firm performance, vertical agency crisis and corporate governance of Indian listed companies

Abstract: PurposeThis study aims to examine the influence of corporate governance variables on firm performance and also to find out whether the corporate governance mechanism is capable of mitigating the vertical agency crisis. Here the researcher uses corporate governance mechanisms such as board meeting frequency, board independence, percentage of non-executive directors, percentage of woman directors on board and the board size to measure the firm performance and, at the same time, tries to mitigate the agency crisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…The weakness in the implementation of corporate governance in Africa is the reason why the existence of independent commissioners has no effect. Similar to research by Sethi et al (2022) India also found that the existence of independent commissioners had no effect and caused conflict in decision-making.…”
Section: The Influence Of Environmental Management On Firm Value Whic...supporting
confidence: 77%
“…The weakness in the implementation of corporate governance in Africa is the reason why the existence of independent commissioners has no effect. Similar to research by Sethi et al (2022) India also found that the existence of independent commissioners had no effect and caused conflict in decision-making.…”
Section: The Influence Of Environmental Management On Firm Value Whic...supporting
confidence: 77%
“…The table also indicates that the average board size (BS) of the sample firms is 9, while the minimum and maximum members of the boards are 4 and 19 members, respectively. The average leverage (LEV) ratio of total debts of the sampled firms to total assets is 0.234, while the minimum is 0 and the maximum is 8.12, similar to firms operating in India [74]. The average value of firm size and firm age are 7.251 and 13.285, respectively.…”
Section: Descriptive Statistics Resultsmentioning
confidence: 87%
“…Jatana, (2023) provided empirical evidence to the effect that board meetings have a positive association with financial performance. For instance, Sethi et al, (2023) opined that greater frequency of meetings is positively associated with firm performance.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical data was presented by Jatana (2023) to support the notion that board meetings improve financial success. Sethi et al (2023), for example, suggested that higher meeting frequency is favorably correlated with company performance.…”
Section: Board Meetings Attendance and Financial Performancementioning
confidence: 99%